Facial expressions alter the fundamental sound properties of speech (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Literature from across academic disciplines has demonstrated significant links between emotional valence and language. For example, Whissell’s Dictionary of Affect in Language defines three dimensions upon which the emotionality of words is describable, and Ekman’s Theories of Emotion include the perception and internalization of facial expressions. The present study seeks to expand upon these works by exploring whether holding facial expressions alters the fundamental speech properties of spoken language. Nineteen (19) participants were seated in a soundproof chamber and were asked to speak a series of pseudowords containing target phonemes.  The participants spoke the pseudowords either holding no facial expression, smiling, or frowning, and the utterances recorded using a high-definition microphone and phonologically analysed using PRAAT analysis software. Analyses revealed a pervasive gender differences in frequency variables, where males showed lower fundamental but higher formant frequencies compared to females. Significant main effects were found within the fundamental and formant frequencies, but no effects were discerned for the intensity variable. While intricate, these results are indicative of an interaction between the activity of facial musculature when reflecting emotional valence and the sound properties of speech uttered simultaneously.
Keywords: PRAAT; phonology; phoneme; gender differences; pitch